Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS

Air-stable double halide perovskite Cs2CuBiBr6: synthesis and memristor application - Betal, Atanu; Chetia, Anupam; Saikia, Dibyajyoti; Karmakar, Krishnendu; Bera, Ganesh; Dambhare, Neha V.; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2025)
The excellent optical and electronic properties of halide perovskite materials have attracted researchers to investigate this particular field. However, the instability in ambient conditions and toxicity of materials like lead have given some setbacks to commercial use. To overcome these issues, perovskite-inspired materials with less toxic and excellent air-stable materials are being studied. Double perovskite materials are one of the perovskite materials. In this study, we have synthesized air-stable double perovskite Cs2CuBiBr6 using a solution process approach. The characterization of the material revealed that it has excellent crystallinity and high stability. The material shows excellent optical and electronic properties. It can be used in resistive memory devices. It shows stable current-voltage characteristics and analog switching. The ion migration through the active layer and accumulation of charge near the electrode region are the reasons behind the resistive switching.